Linking energy behaviour, attitude and habits, and social practices with environmental predisposition and knowledge:what are the factors with influence on environmental behaviour? - Pothitou, Mary (Cranfield University, 2015)
This research aims to understand which factors influence environmental behaviour in order to contribute to the existing theory and practice which is focused on individuals' energy consuming behaviour. As a first step, this thesis reviews existing up-to-date literature related to individual household energy consumption. The how and why individual behaviour affects the energy use are discussed, together with the principles and perspectives which have so far been considered in order to explain the habitual consuming behaviour. The research gaps, which are revealed from previous studies in terms of the limitations or assumptions of the methodology with respect to altering individuals’ energy usage, give insights for a conceptual framework to define a comprehensive approach which attempts to contribute to existing theory. The proposed framework suggests that the individual energy perception gaps are affected by psychological, habitual, structural and cultural variables in a wider-contextual (i.e. national scale), meso-societal and micro-individual spectrum. All these factors need to be considered in order for a variety of combined intervention methods, which are discussed and recommended, to introduce a more effective shift of the conventional energy consuming behaviour, advancing insights for successful energy policies. Furthermore, this thesis presents and discusses the findings of an empirical study which compares individuals’ environmental predisposition and knowledge with their: (a) energy behaviour, attitude and habits; and (b) social practices related to the use and ownership of appliances. This study also attempts to correlate education level and household income with the above variables. The investigation is based on a survey of 68 employees of an educational institution, corresponding to a medium-sized enterprise, which was selected as the first phase of research aiming to compare energy saving behaviour at home and in the workplace. The current study relates only to the domestic aspects of this work attempting to contribute to existing practice by presenting a detailed evaluation of pro-environmental behaviour which can be applied to similar studies while considering different demographics. In particular, the sample of this study is composed of a relatively highly educated and professional population. The statistical analysis reveals significant correlations between environmental value and knowledge and elements of individuals’ energy attitudes, habits and behaviour. The respondents’ predisposition and attitudes is further correlated with social practices associated with domestic appliances. No significant correlations were established to demonstrate that education level may influence environmental predisposition and knowledge, energy saving attitudes, habits and behaviours however, given the nature of the population sample, this is not surprising. An unanticipated outcome from the Principal Component Analysis (PCA) was that household income, and to a lesser extent gender, are associated with energy saving habits and behaviours. On further investigation, household income was found to be correlated with knowledge of greenhouse gas emissions and the number of laptops and electric showers owned per household. Conversely, a relationship between individuals’ energy habits and household consumption practices was not indicated by significant correlations.
Keywords: Pro-environmental behaviour; energy behaviour; attitudes; habits; social practices; environmental predisposition; environmental knowledge